The importance of business zakat as a financial vehicles on economic and social wellbeing: The empirical study in Kelantan - Ab Rahman , Siti Maziah; Ismail, Md Khairu Amin; Yusof , Azahar (Journal of Islamic, Social, Economics and Development, 2024)
Business zakat plays a crucial role in promoting economic and social well-being within Islamic finance. It serves as a financial vehicle that redistributes wealth, supporting community welfare and poverty alleviation. By mandating a 2.5% contribution from business profits, zakat encourages ethical business practices and enhances corporate social responsibility. This practice not only fosters economic stability but also strengthens social cohesion by addressing inequalities. Ultimately, business zakat contributes to sustainable development goals, aligning financial success with moral obligations in society, thereby enhancing overall community welfare and resilience. Business zakat is essential for fostering economic growth and social equity within Islamic finance. This practice encourages ethical business operations and corporate social responsibility, aligning financial success with moral obligations. Additionally, business zakat strengthens community ties and promotes sustainable development by addressing income disparities. By integrating zakat into business practices, companies not only fulfill religious duties but also contribute to broader economic stability and societal well-being. This study explores the significance of business zakat as a financial vehicle for enhancing economic and social wellbeing in Kelantan, Malaysia. It examines the effective zakat distribution can alleviate poverty, empower small and medium enterprises (SMEs), and promote social justice. The research identifies barriers to zakat compliance among entrepreneurs, including lack of awareness and technological access. By focusing on e-zakat adoption, the study aims to propose strategies that can improve zakat collection and utilization, ultimately fostering sustainable economic growth and improving the quality of life for marginalized communities in Kelantan.